A cimentação da vida laboral dos trabalhadores da construção civil - Adriana García Martínez (2019)
The foundation comprises the construction stage of the basic structure of a building and this process is taken as an analogy to analyze the consolidation of the working life of civil construction workers. It is part of the context of changes in the world of work and in cities, which since the end of the 1970s includes the development of new forms of contemporary capitalism -with the implementation of new production processes- and the new modeling of the corresponding urban landscape to global patterns. These processes brought elements that impacted the civil construction sector and influenced, in a decisive way, the corresponding labor market and the population employed in this sector. Social groups that historically have faced an accumulation of social disadvantages and that, with the increase of unemployment, flexibility and job precariousness, find in civil construction an employment opportunity form this. However, they have to deal with the specificities of the construction process and with old and new labor practices to stay in the labor market. How is the work life of civil construction workers "grounded"? It is the question that guides this investigation. This social process was analyzed based on a qualitative approach and a cut that considered two Latin American cities: Belo Horizonte and Mexico City. The work trajectories of men and women employed during the field work period, carried out between the second semester of 2017 and the first semester of 2018, were addressed. The interaction with this population occurred in a school and outside the works where They conducted targeted conversations and interviews that sought to rescue the life stories of men and women of different ages. The information obtained allowed us to identify four types of work trajectories associated with the time and work experience of each worker in civil construction: continuous, new-entry, reintegration and temporary. It also showed that it is still the male population that has the most presence and permanence in this sector, which justifies its leading role in this research, although the female population is included. When analyzing the interrelation of changes, social aspects, work dynamics and work trajectories, it is concluded that the workers are responsible for building the columns that allow them to build their working life. Thus, acceptance, demand, adaptability and availability are the bases that contribute to maintaining the labor market in this sector. This process shows a reality that does not depart from what is currently arising in the world of work of contemporary capitalism, but has its own peculiarities by the characteristics of the productive process and recruitment of labor that has civil construction.